Adapting the wellness offer in Slovenian spas to the new COVID-19 pandemic conditions. Issue 3 (2nd September 2022) - Rančić Demir, Milica; Pavlakovič, Barbara; Pozvek, Nejc; Turnšek, Maja
ABSTRACT: The COVID-19 pandemic has had a markedly negative impact on global tourism and, on the other hand, has offered new opportunities for researchers to analyze the resilience of the tourism industry in such conditions. Recently, several scientific articles have emerged claiming that the COVID-19 pandemic could represent an opportunity for significant changes in tourism. This refers to changing practices at several levels and spreading new ethical principles. The pandemic has also made people aware of the importance of "well-being". Even without a pandemic, wellness tourism has been one of the fastest-growing types of tourism in recent years. In all parts of the world, including Slovenia, natural spas have tried to adapt to new conditions during the COVID-19 pandemic. Our analysis confirms that visitors to Slovenian spas strongly support introducing new/alternative activities and thus the dispersion of visitors to several locations. They showed the greatest interest in visiting nature in the vicinity of spas, which is also expected as a result of the closure during the pandemic. The purpose of our article is to give suggestions for offering alternative activities in Slovenian natural spas. However, adapting the wellness offer in spas should ensure that the basic traditional principles of wellness are maintained.